Sequential intussusception in a set of female twins - Osoka, Vincent Uchechukwu; Egbuchulem, Ifeanyichukwu Kelvin; Oyedeji, Peter Oluwatoyin; Olulana, Dare Isaac; Ogundoyin, Olakayode Olaolu; Ajao, Akinlabi Emmanuel (Journal of Global Medicine, 2025)
Introduction: Intussusception is the leading cause of intestinal obstruction in children in sub-Saharan Africa. Familial occurrences of intussusception have been reported. Simultaneous or concurrent twin intussusception is rarely reported, particularly in Africa. Case presentation: We report a case of intussusception in 5-month-old dizygotic female twins occurring 18 days apart in Southern Nigeria. The younger twin presented at our facility with symptoms including vomiting, the passage of red currant jelly stool, and abdominal distension for 4 days. She subsequently experienced a seizure and underwent a right hemicolectomy for a perforated gangrenous ileocolic intussusception. Eighteen days later, the old twin presented with vomiting and the passage of red currant jelly stool for 1 day. She successfully underwent an ultrasound-guided hydrostatic reduction of her ileocolic intussusception. Conclusion: The exact cause of sequential twin intussusception is not entirely understood; however, it appears to be multifactorial. It seems that twins with similar systemic inflammatory responses, combined with congenital anatomical and genetic predispositions, are more likely to develop intussusception when simultaneously exposed to the same trigger.